Local taxation - Anderson, William (My University, 1898)
Introduction: In making this study, it shall be our attempt to show what a true tax should contain, after which we shall treat the subject from a purely local standpoint, taking up the method of assessment in Kansas, and a special investigation of taking and assessing property in Riley and Pottawatomie counties. If after making this investigation, we find remedies we deem necessary we shall not hesitate to suggest them. Our effort however, will chiefly be to show what the present conditions are leaving conclusions to be drawn from there to the reader.
Citation: Anderson, William. Local taxation. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: True Tax; Kansas; Investigation; Theses; Manuscripts (documents)